Forming conservation ambassadors: an education and training-based hr development program at semarang zoo - Lahagu, Aristo; Pranoto, Pranoto (International Journal on Social Science, Economics and Art, 2024)
The management of Semarang Zoo has taken significant steps to improve the quality of services and conservation through the impact of the development and implementation of more modern and inclusive Human Resource management practices. This study presents an observational analysis of how the organizational structure, jobdesk, job requirements, planning and assessment of human resource performance, recruitment process, and human resource problems in Semarang Zoo are present. The research method used is an ethmomethodological approach that involves observation, interviews, and in-depth understanding and interaction regarding Human Resource Management at the destination. The results show that Semarang Zoo has a structure and jobdesk with the aim that the zoo can be managed into a recreational place that has conservation and educational value. Employee characteristics play an important role, there are job opportunities that offer a degree of flexibility depending on the size of the risk. Decisions are not just black on white, but depend on employee experience. Planning and assessing Human Resources performance are also carried out to anticipate problems that will occur in the future. However, the problems that arise can be solved because there are suitable solutions to overcome them. The reference at Semarang Zoo is reflected through the existence of structured management procedures. Knowledge of this is important in the development of conceptual and sustainable tourism management.